The Relationship between Family Support and Exclusive Breastfeeding among Breastfeeding Mothers at The Posyandu in Weragati Village, Palasah Subdistrict, Majalengka Regency, in 2025 - Sumarni Sumarni; Uun Kurniasih; Sri Lestari; Lin Herlina; Siti Halisa Nurlailasari (Devotion : Journal of Research and Community Service, 2026)
Exclusive breastfeeding is an important effort to improve infant health outcomes. However, the coverage of exclusive breastfeeding remains below the national target. One of the factors influencing the success of exclusive breastfeeding is family support. This study aimed to analyze the relationship between family support and exclusive breastfeeding among breastfeeding mothers at the Posyandu in Weragati Village, Palasah Subdistrict, Majalengka Regency. The study employed a quantitative approach with a cross-sectional design. The study population consisted of 51 breastfeeding mothers with infants aged 6–24 months, and a total sampling technique was applied, resulting in all members of the population being included as research participants. Data were collected using questionnaires that had been tested for validity and reliability, then analyzed using univariate and bivariate analyses with the Chi-square test. The results showed that the majority of respondents received high levels of family support, accounting for 46 respondents (90.2%), and 38 respondents (74.5%) practiced exclusive breastfeeding. The bivariate analysis revealed a p-value of 0.012 (p < 0.05), indicating a significant relationship between family support and exclusive breastfeeding among breastfeeding mothers. Family support was significantly associated with the success of exclusive breastfeeding. Higher levels of family support increased the likelihood that mothers would provide exclusive breastfeeding. Therefore, family involvement should be strengthened through education and health promotion programs to support the successful implementation of exclusive breastfeeding initiatives.